Assessing Preventability for Obstetric Hemorrhage - Della Torre, Micaela; Kilpatrick, Sarah J.; Hibbard, Judith U.; Simonson, Louise; Scott, Shirley; Koch, Abby; Schy, Deborah; Geller, Stacie E. (American Journal of Perinatology, 2011)
We sought to determine preventability for cases of obstetric hemorrhage, identify preventable factors, and compare differences between levels of hospital. We retrospectively reviewed a 1-year cohort of severe and near-miss obstetric hemorrhage in an urban perinatal network. An expert panel, using a validated preventability model, reviewed all cases. Preventability and distribution of preventability factors were compared between levels of hospital care. Sixty-three severe and near-miss obstetric hemorrhage cases were identified from 11 hospitals; 54% were deemed potentially preventable. Overall preventability was not statistically different by level of hospital, and 88% were provider related. The only treatment-related preventability factors were significantly different between levels of hospital and significantly less common in level III hospitals (p < 0.01). The majority of obstetric hemorrhage was preventable. The most common potentially preventable factor was provider treatment error, and this was significantly more common in level II hospitals. New interventions should be focused on decreasing providers' treatment errors.
Keywords: Preventability; maternal morbidity and mortality; near miss; obstetric hemorrhage